A Study of Turn Taking Used in Radio Talk Show Under the Topic “Gender Equality and Women’s Empowerment” - Nuri Saraswati; Waode Hamsia (Tell : Teaching of English Language and Literature Journal, 2017)
This research analyzed about the using of turn-taking as the strategy in the radio talk show at Hard Rock FM in the topic Gender Equality and Women's Empowerment, the guest was Myra Brown. It was analyzed because the researcher considered that turn-taking was one of strategies of language. The research approach was descriptive qualitative. ItÂ  identified the types of turn-taking, the speakers' strategies, some reasons that the speakers took the turn, and the relation among the speakers after they took the turn. The main theories that the researcher used were discourse analysis by Gee (2011), turn-taking by Renkema (2004), and context by van Dijk (2009). This research discovered that there were three types of turn taking. They are speaker's selection, speaker's self choice, and speaker's determination. Strategies that are used by the speakers, they are overlap, interruption, back-channel, and silence. One of the reasons that the speakers took the turn was that the hosts dig information from the guest related with the topic.